(untitled) (Research, Society and Development, 2020)
Introduction: Pressure injury (LP) is a recurrent complication in critically ill patients and is related to the rehabilitation and quality of life of individuals. LP’s are considered adverse events as they are related to the quality of care provided during hospitalization. The development of mobile applications incorporated into scientific research is an important tool for assistance, due to the process of analysis and testing with professionals who know the real needs of end users. Recognizing the demands of the target audience is essential to plan and implement new technologies in a coherent and appropriate manner, according to specific requirements, tested in research and implemented in practice. Objective: To develop software guided by the nursing process to assist the nurse in the evaluation and treatment of Pressure Injury. Methodology: Descriptive and exploratory methodological research, with a quantitative approach, where the software development process involved bibliographic research of significant studies on the theme, serving as a database for the creation of the mobile application and its tools. The software interface, icons and navigation environment were created using the React Native programming language. The software development process was based on the Waterfall method, which comprises the phases of: definition of system requirements, software requirements, process analysis, Design, Coding, Tests and Implementation. Results: The created application has an intuitive and easy to navigate interface where the patient’s demographic data, physical examination and lesion characteristics are inserted and saved. It allows the nursing professional to have practicality and efficiency in the evaluation and treatment of LP based on the nursing process. Final Considerations: The application proved to be reliable and functional for the evaluation and treatment of LP, based on the tests carried out, being able to move on to the next stage of validation and registration of the application, in order to become in fact a product available to assist the nursing professional in their clinical practice.